2014
DOI: 10.1007/s00401-014-1256-4
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation active immunization approach for synucleinopathies: implications for Parkinson’s disease clinical trials

Abstract: Immunotherapeutic approaches are currently in the spotlight for their potential as disease-modifying treatments for neurodegenerative disorders. The discovery that α-synuclein (α-syn) can transmit from cell to cell in a prion-like fashion suggests that immunization might be a viable option for the treatment of synucleinopathies. This possibility has been bolstered by the development of next-generation active vaccination technology with short peptides-AFFITOPEs® (AFF) that do not elicit a α-syn specific T-cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
189
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 208 publications
(197 citation statements)
references
References 82 publications
6
189
1
1
Order By: Relevance
“…These results suggested that α-syn vaccination is effective in reducing neuronal accumulation of α-syn aggregates and that further development of this approach might have a potential role in the treatment of synucleinopathies. Other active immunization approaches using AFFITOPEs (AFFiRiS AG) that mimic abnormal conformations of α-syn have been studied in animals model of PD and MSA [65,66]. AFFITOPEs that mimic the C-terminus region of α-syn are able to elicit an immune response specific to α-syn oligomers [66].…”
Section: Immunotherapy Targeting Aβmentioning
confidence: 99%
See 4 more Smart Citations
“…These results suggested that α-syn vaccination is effective in reducing neuronal accumulation of α-syn aggregates and that further development of this approach might have a potential role in the treatment of synucleinopathies. Other active immunization approaches using AFFITOPEs (AFFiRiS AG) that mimic abnormal conformations of α-syn have been studied in animals model of PD and MSA [65,66]. AFFITOPEs that mimic the C-terminus region of α-syn are able to elicit an immune response specific to α-syn oligomers [66].…”
Section: Immunotherapy Targeting Aβmentioning
confidence: 99%
“…Other active immunization approaches using AFFITOPEs (AFFiRiS AG) that mimic abnormal conformations of α-syn have been studied in animals model of PD and MSA [65,66]. AFFITOPEs that mimic the C-terminus region of α-syn are able to elicit an immune response specific to α-syn oligomers [66]. Vaccination with one of these AFFITOPEs (AFF 1) resulted in high antibody titers against α-syn aggregates, decreased accumulation of α-syn oligomers, reduced degeneration of tyrosine hydroxylase fibers in the caudoputamen nucleus, and improved motor and memory deficits in 2 α-syn transgenic models [66].…”
Section: Immunotherapy Targeting Aβmentioning
confidence: 99%
See 3 more Smart Citations